XXX the next level - Tamahori, Lee; Kinbert, Simon; Moritz, Neal H.; Schmidt, Arne L.; Revolution Studios (Culver City, CA : Sony Pictures Home Entertainment, 2005)
Darius Stone is an imprisoned Navy SEAL, activated by an NSA agent to stop an assassination plot targeting the president
Features: audio commentary, deleted scenes, featurettes, trailers
Title from title screen
Cinematographer, David Tattersall ; editors, Mark Goldblatt, Todd E. Miller, Steven Rosenblum ; music, Marco Beltrami ; costume designer, Sanja Milkovic Hays ; production designer, Gavin Bocquet
Cast: Ice Cube, Samuel L. Jackson, Willem Dafoe, Scott Speedman, Peter Strauss, Xzibit, Michael Roof, Sunny Mabrey, Nona Gaye, John G. Connolly
DVD Format
In English or Thai with optional Chinese, English, Korean or Thai subtitles
Keywords: Presidents -- Assassination attempts -- Drama; Adventure films; Conspiracies -- Drama; Criminals -- Drama; Punishment -- Drama